2013
DOI: 10.1115/1.4025566
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Control of an Electrically Assisted Tensile Forming Process Using Current Modulation

Abstract: Electrically assisted forming is a technique whereby metal is deformed while simultaneously undergoing electric current flow. Using this process, electric current level becomes a new degree of freedom for process control. In this work, we present some alternative control architectures allowing for new avenues of control using such a process. The primary flndings are architectures to allow for forming at constant force and forming at constant stress levels by modulating electric current to directly control mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…EPE has been observed in materials possessing different crystal structure, electrical resistivity and thermal conductivity, and deformed under different conditions. 124 In a recent work, 20 a decrease of the electrical threshold as the material resistivity increased has been noted, but no relations between lattice type and EPE were revealed; this reduction in the threshold value may support the theory of localised heating from electrons scattering-off from lattice obstacles, allowing the lattices to expand easier. Further, in some cases, it has been observed a possible effect on the material flow stress that appears to be solely due to the electrical influence, beyond what would be expected from the temperature effects.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…EPE has been observed in materials possessing different crystal structure, electrical resistivity and thermal conductivity, and deformed under different conditions. 124 In a recent work, 20 a decrease of the electrical threshold as the material resistivity increased has been noted, but no relations between lattice type and EPE were revealed; this reduction in the threshold value may support the theory of localised heating from electrons scattering-off from lattice obstacles, allowing the lattices to expand easier. Further, in some cases, it has been observed a possible effect on the material flow stress that appears to be solely due to the electrical influence, beyond what would be expected from the temperature effects.…”
Section: Introductionmentioning
confidence: 96%
“…In the past years, many efforts have been spent on the study of the effect of electricity within metals during deformation, in order to understand in which extent the application of continuous and pulsed electrical current can induce enhancements on their formability. Starting from the pioneering works of Conrad and Troitskii, 13 the researchers involved in the study of the so-called electroplasticity have performed numerous experiments on a wide range of metals and alloys, 424 leading to the development of theories explaining the phenomenon known as electro-plastic effect (EPE). These works have revealed that the passage of electricity can cause a modification of the materials flow properties by improving their workability, therefore making this method suitable to be adopted in forming operations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation